Lichen diversity and taxonomy in Bukit Barisan Grand Forest Park, North Sumatra, Indonesia - OKY KUSUMA ATNI; ERMAN MUNIR; ETTI SARTINA SIREGAR; M. N. SALEH (Society for Indonesian Biodiversity, 2024)
Abstract. Atni OK, Munir E, Siregar ES, Saleh MN. 2024. Lichen diversity and taxonomy in Bukit Barisan Grand Forest Park, North Sumatra, Indonesia. Biodiversitas 25: 1623-1630. Located in Bandar Baru Village, Deli Serdang District, North Sumatra, Bukit Barisan Grand Forest Park stands out for its uniqueness and high biodiversity, including lichens. This study aims to identify and map lichen diversity in the research area. Surveys were conducted from January to February 2024 using an exploratory method along designated tracks. Therefore, 57 lichen species from 23 families and 38 genera were found. Based on their thallus types, 26 lichen species were identified as crustose, 17 as foliose, 6 as squamulose, 5 as fruticose, and 3 as filamentous. Reproductive structures varied, 13 species possessed apothecia, soredia, and lacked distinguishable reproductive structures, 10 had lirellae, 7 had perithecia, and 2 had isidia. Graphidaceae emerged as the most prevalent family with 8 species, predominantly growing on bark substrates. Although lichen distribution correlated with pH levels, its correlation with the preference for lower pH levels was low. Host trees from the Pinaceae and Lauraceae families were the most populated by lichens in this study. Research on lichen diversity in Bukit Barisan Grand Forest Park is crucial, considering the increasing development and deforestation in North Sumatra. A more comprehensive study of lichens is urgently required.